"Yang Lain" Dalam Pemikiran Levinas dan Ricoeur Terkait Prinsip Hidup Bermasyarakat - John C. Simon (Indonesian Journal of Theology, 2018)
Levinas and Ricoeur share a concerted attention for the Other. Each bases his thought upon the understanding that philosophy ought primarily be construed as ethics, with a political dimension able to transform life unto justice. However, each also approaches the task of justice differently. Levinas adopts an asymmetric ethic that I should do justice to the poor, the stranger, the marginalized and the orphaned, yet without expecting anything in return. For him, such responsibility precedes one’s being. On the other hand, Ricoeur adopts a symmetrical and reciprocal ethics, where the praxis of a good and just life resembled collaboration, where each person contributes ideas and efforts to promote that very same good and just life. Ricoeur likewise sounds an ethical call for justice within institutions, such as the nation-state that becomes a vehicle for collaborate efforts toward justice. Asymmetrical as well as symmetrical ethical callings signal equally vital elements for the construction of a contextual political theology in Indonesia. This article highlights two crucial themes in fair economic behavior and religiously based communalism. Within the frame of a democratic nation-state, the communalistic nature of Pancasila can serve as a means for political theologizing that shifts the orientation from center to periphery.